2021
DOI: 10.33073/pjm-2021-012
|View full text |Cite
|
Sign up to set email alerts
|

First Description of Various Bacteria Resistant to Heavy Metals and Antibiotics Isolated from Polluted Sites in Tunisia

Abstract: Environmental bacteria belonging to various families were isolated from polluted water collected from ten different sites in Tunisia. Sites were chosen near industrial and urban areas known for their high degree of pollution. The aim of this study was to investigate cross-resistance between heavy metals (HM), i.e., silver, mercury and copper (Ag, Hg, and Cu), and antibiotics. In an initial screening, 80 isolates were selected on ampicillin, and 39 isolates, retained for further analysis, could grow on a Tris-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Walsh and Caslake (2016) showed a significant relationship between mercury and multi-antibiotic resistance in E. coli isolated from the aquatic environment. Another study reported that there is cross-resistance between various antibiotics and silver, copper, and mercury in bacteria isolated from polluted water (Miloud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Walsh and Caslake (2016) showed a significant relationship between mercury and multi-antibiotic resistance in E. coli isolated from the aquatic environment. Another study reported that there is cross-resistance between various antibiotics and silver, copper, and mercury in bacteria isolated from polluted water (Miloud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of QACs, azoles, chlorhexidine, and metals in the environment has led to concerns that these biocide classes may persist in wastewater facilities from hospitals and food processing plants, as well as in run-off from agriculture. Several studies detected low levels of biocidal chemicals in wastewater, food, soil, mines, and other environmental sources [ 77 , 78 , 110 , 117 , 119 ]. Researchers hypothesize that biocide-tolerant bacteria rising from low concentration exposure in these niche environments may result in biocide-mediated antibiotic cross-resistance development in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of efflux pump proteins and a reduced expression of porins have been described as possible mechanisms of metal tolerance [ 74 , 75 ], as well as an enzymatic reduction of the cation to the metal [ 60 , 70 ]. Generally, authors have reached the agreement that the exact mechanisms still remain unclear and are also organism specific [ 76 , 77 , 78 , 79 ]. Therefore, further investigation is needed.…”
Section: Biocides—major Classes Chemistries Modes Of Action and Resis...mentioning
confidence: 99%
See 1 more Smart Citation
“…And the antibiotics suspension (0.3 ml) was transferred to the well. The plates were then kept at 37°C for a further 24 hours [22], [23].…”
Section: Determination Of Antibiotic Susceptibilitymentioning
confidence: 99%